Verbal Aggression in Political Discourse - Hirschová, Milada; Svobodová, Jindřiška (Bohemica Olomucensia, 2015)
The paper deals with the phenomenon of verbal aggression as a specific communicative strategy in interpersonal exchanges, in mass media and in political discourse. It aims at the differences the notions and manifestations of im/politeness, rudeness and verbal aggressivity. In the broader framework of social interaction, aggressive communication occurs in two forms: a/ as a hostile aggression which is impulsive, driven by anger and primarily aiming at harming the target; b/ as an instrumental aggression which is premeditated as a means of retaliation or obtaining some goal (e.g., to boost up speaker's position). The latter seems to be the most frequent feature in political discourse. Presented samples of dialogues have demonstrated that the aggressive/openly offensive communication can be seen not just as a borderline case of impoliteness but, more accurately, as a parallel phenomenon, a communicative strategy which can use vulgarities but can dispense with them as well.
Keywords: aggressivity; verbal aggression; im/politeness; rudeness; offense; personal identity attack; self presentation; explicit vs implicit dehonestation